2017
DOI: 10.1002/anie.201701347
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Aza‐ullazines

Abstract: A range of aza-ullazines, which represent a new heterocyclic core structure, were synthesized through a scalable four-step reaction, including a Sonogashira reaction and metal-free cyclization promoted by p-toluenesulfonic acid. The optical and electrochemical properties of selected derivatives were investigated, they were found to have similar absorption and emission spectra but a higher oxidation potential than the parent ullazine core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 56 publications
4
58
0
Order By: Relevance
“…19 Next, a Sonogashira cross-coupling reaction was selected to prepare compounds 4a-c. Previous reports used either P( t Bu) 3 13 or di-1-adamantyl-n-butylphosphine (cataCXium® A) 18 as oxygen sensitive phosphines for 24 hours as reaction time. In our case, we optimized the reaction conditions using standard PdCl 2 (PPh 3 ) 2 /CuI and the less air sensitive PPh 3 as catalytic system, together with microwave irradiation as heating source.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…19 Next, a Sonogashira cross-coupling reaction was selected to prepare compounds 4a-c. Previous reports used either P( t Bu) 3 13 or di-1-adamantyl-n-butylphosphine (cataCXium® A) 18 as oxygen sensitive phosphines for 24 hours as reaction time. In our case, we optimized the reaction conditions using standard PdCl 2 (PPh 3 ) 2 /CuI and the less air sensitive PPh 3 as catalytic system, together with microwave irradiation as heating source.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Recently, Boldt et al reported on the synthesis of aza-ullazine derivatives in a metal-free cyclization promoted by ptoluenesulfonic acid for the first time. 18 However, the presence of an additional nitrogen atom on the periphery did not lead to any noticeable modification of the photophysical properties in comparison with parent ullazine derivatives.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Overall, the synthesis and purification of 4 b was easier compared to 4 a . The pyridinic half of the molecule with the pre‐formed bonds at the 3/5 positions was prepared starting from 4‐aminopyridine which was brominated with N ‐bromosuccinimide (NBS) via standard procedures [15] . The obtained di‐brominated derivative 6 was then subjected to Suzuki couplings either with phenylboronic acid for 7 a or with 3‐ tert ‐butylphenylboronic acid for 7 b .…”
Section: Figurementioning
confidence: 99%